2019
DOI: 10.33808/clinexphealthsci.563988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxicity Risk in Health Care Workers Exposed to Antineoplastic Drugs

Abstract: Objective: DNA damage that can be caused by workplace exposure to antineoplastic drugs in health workers has been shown in many scientific studies. It is aimed to evaluate whether the risk of genotoxicity in health workers decreases after the regulations and measures taken by national and international health authorities in our work. Methods: For this purpose, DNA damage was assessed by using alkaline comet technique in lymphocytes isolated from blood samples of health workers (n=29) who were involved in prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(35 reference statements)
1
3
0
2
Order By: Relevance
“…In our study, we noticed the insignificantly increased DNA damage in a group of workers exposed to ANTNP in comparison to non-exposed volunteers. The recorded result is in accordance with many studies in which, besides MN test, DNA damage was confirmed by chromosomal aberration, sister chromatid exchange and comet assays [22][23][24]. This result, as well as conclusions of our previous study on the same group of hospital workers [3] could be explained in relation to the protective equipment (gloves, masks, goggles and cabin) that was not used adequately to completely prevent exposure to genotoxic xenobiotics [22].…”
Section: Dna Damagesupporting
confidence: 90%
“…In our study, we noticed the insignificantly increased DNA damage in a group of workers exposed to ANTNP in comparison to non-exposed volunteers. The recorded result is in accordance with many studies in which, besides MN test, DNA damage was confirmed by chromosomal aberration, sister chromatid exchange and comet assays [22][23][24]. This result, as well as conclusions of our previous study on the same group of hospital workers [3] could be explained in relation to the protective equipment (gloves, masks, goggles and cabin) that was not used adequately to completely prevent exposure to genotoxic xenobiotics [22].…”
Section: Dna Damagesupporting
confidence: 90%
“…From the 21 articles read in full, 2 were excluded because they did not present comet assay data. Nineteen studies of occupational exposure [ 12 , 16 , 191 , 196 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ] remained for qualitative analysis, as summarised in Figure 3 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of studies on the genotoxic effects of antineoplastic drugs using the comet assay in occupationally exposed workers are inconsistent, but a slightly positive association exists. Overall, 13 studies (68.4%) showed a statistically significant increase in DNA damage in the exposed group compared with the controls [ 12 , 191 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 208 , 211 , 212 , 213 , 214 ]. Ursini (2006) showed positive results for both biological matrices under study—lymphocytes and buccal cells [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…Para la mayoría de los citostáticos, se postula una curva dosis-respuesta lineal para los efectos genotóxicos, sin un efecto de dosis umbral perceptible (efectos de tipo estocástico). (10,18) En 2011, en el Centro Oncológico de Egipto, se muestrearon 28 trabajadores expuestos a citostáticos, entre farmacéuticos y enfermeras, y se evidenció que el número de linfocitos aberrantes, así como la aberración cromosómica y las frecuencias de micronúcleos, fueron significativamente mayores en el personal expuesto en comparación con los controles pareados. En comparación con los farmacéuticos, las enfermeras mostraron notablemente mayor nivel de daño cromosómico.…”
Section: Discussionunclassified